Emotions and identity - Zerbe, W. J.; Hartel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945-; Petitta, Laura (Research on emotion in organizations ;, 2017)
This volume focuses on the crucial role of emotions in forming and sustaining individual and collective identities at work. In addition, it explores the outcomes and boundaries of such identities while recognizing the driving role of emotions at various organizational levels, acknowledging that the relationship between emotion and identity is multifaceted and can be explored from various points of view. Identities and emotions are constantly evolving and are central aspects of organizational behavior, from the front-line interactions of employees to the broader ideological forces that shape institutions and organizational cultures. Thus, this volume recognizes the depth of emotion and identity at work by addressing these topics on individual, group, occupational, and social role levels. This volume is organized in four parts to contribute clearly to each of these areas of inquiry. Part 1 focuses on the micro-level topics of identity, anger and diversity. Part 2 focuses on the role of emotions in public sector settings, Part 3 focuses on the relationships between gender, emotions and identity, while Part 4 investigates how emotions influence individual identification with work.